The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3177/jnsv.63.306
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Three Tea Cultivars (<i>Camellia sinensis</i> L.) on Nitric Oxide Production and Aortic Soluble Guanylate Cyclase Expression in High-Salt Diet-Fed Spontaneously Hypertensive Rats

Abstract: Summary Studies have suggested that the consumption of green tea reduces the risk of cardiovascular diseases. Although epigallocatechin gallate (EGCG) is the best studied active substance characteristic of green tea, previous results on EGCG do not appear sufficient to explain completely the mechanism of cardiovascular protection by green tea. Therefore, we investigated the effect of three different tea cultivars, "Yabukita," "Sofu," and "Sunrouge," which have characteristic flavonoid compositions, on the nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This study revealed that black tea extract prevented elevated plasma homocysteine levels and downregulated endoplasmic reticulum stress markers. Furthermore, Nomura et al (2017) [59] investigated the protective effect of three different cultivars of Camellia sinensis ("Yabukita", "Sofu" and "Sunrouge") in a model of hypertensive rats fed with a high salt diet. All these tea cultivars reduced urinary NO metabolite and, moreover, "Yabukita" and "Sofu" increased soluble guanylate cyclase expression.…”
Section: Camellia Sinensis and Hypertensionmentioning
confidence: 99%
“…This study revealed that black tea extract prevented elevated plasma homocysteine levels and downregulated endoplasmic reticulum stress markers. Furthermore, Nomura et al (2017) [59] investigated the protective effect of three different cultivars of Camellia sinensis ("Yabukita", "Sofu" and "Sunrouge") in a model of hypertensive rats fed with a high salt diet. All these tea cultivars reduced urinary NO metabolite and, moreover, "Yabukita" and "Sofu" increased soluble guanylate cyclase expression.…”
Section: Camellia Sinensis and Hypertensionmentioning
confidence: 99%
“…In an experiment involving SHRs fed large quantities of salt, the effects of the 3 green tea varieties “Yabukita,” “Sofu,” and “Sunrouge” on NO production were investigated. 87 It was observed that the reduction in NO production caused by high salt intake could be prevented on the intake of all the varieties of teas in SHRs. The long-time consumption of “Sofu” and “Sunrouge” was also shown to increase the aortic expression of available guanylate cyclase in SHRs.…”
Section: Introductionmentioning
confidence: 99%